Driving digital maturity in the Portuguese healthcare system: An empirical study on digital literacy and inclusion through structural equation modelling - Geada, N.; Alturas, B. (Education for Information)
The digital transformation of healthcare is a strategic priority, but its success depends on human and organizational factors. While research has examined digital literacy and maturity, little is known about how individual skills and inclusive practices shape organizational progress. This study addresses this gap by analysing the impact of Digital Literacy (DL) and Digital Inclusion (DI) on Digital Maturity (DM) in healthcare. Using a quantitative design and Structural Equation Modelling (SEM), results confirm that DL and DI are significant drivers of DM. Notably, DI emerges as a crucial mediator, showing that organizational maturity relies not only on stakeholders’ capabilities but also on equitable access and support structures. These insights emphasize that effective digital transformation must adopt human-centric strategies, prioritizing literacy and inclusion to ensure sustainable progress. By integrating these factors, healthcare organizations can strengthen digital maturity and achieve meaningful transformation outcomes.